The Counselling and psychotherapy research handbook - Vossler, Andreas; Moller, Naomi (Los Angeles SAGE, 2015)
Setting the scene. Why research matters/ Andreas Vossler, Naomi Moller & Mick Cooper -- Attitudes to and perceptions of research/ Andreas Vossler & Naomi Moller -- Beginning the research journey -- Choosing a research question/ Elaine Kasket -- How to read and understand research/ Elena Gil-Rodiguez -- Doing a literature review/ Meg Barker -- Introduction to research methodology/ Ladislav Timulak -- Planning your research: Design, method and sample/ Terry Hanley, Clodagh Jordan & Kasia Wilk -- Ethical considerations/ Tim Bond -- Writing a research proposal/ Mark Donati -- Methodologies and methods for doing research -- Quantitative methods/ Elspeth Twigg -- How to use t-tests to explore pre-post change/ Elspeth Twigg & Paul Redford -- Qualitative methods Linda Finlay -- How to use thematic analysis with interview data/ Virginia Braun, Victoria Clarke & Nicola Rance -- Case studies methodologies/ Julia McLeod, Mhairi Thurston & John McLeod -- How to use case study methodology with single client therapy data/ Mhairi Thurston, Julia McLeod & John McLeod -- Completing the research journey -- Dissemination of research/ Andrew Reeves -- Student top tips/ Brian Sreenan, Harriet Smith & Charles Frost -- Next steps. Building on and using research in training and practice/ Peter Stratton, Naomi Moller & Andreas Vossler.
pt. I Introduction -- 1. Setting the scene: Why research matters (Andreas Vossler, Naomi Moller & Mick Cooper) -- 2. Attitudes to and perceptions of research (Andreas Vossler & Naomi Moller) -- pt. II Beginning the research journey -- 3. Choosing a research question (Elaine Kasket) -- 4. How to read and understand research (Elena Gil-Rodriguez) -- 5. Doing a literature review (Meg Barker) -- 6. Introduction to research methodology (Ladislav Timulak) -- 7. Planning your research: Design, method and sample (Terry Hanley, Clodagh Jordan & Kasia Wilk) -- 8. Ethical considerations (Tim Bond) -- 9. Writing a research proposal (Mark Donati) -- pt. III Methodologies and methods for doing research -- 10. Quantitative methods (Elspeth Twigg) -- 11. How to use t-tests to explore pre-post change (Elspeth Twigg & Paul Redford) -- 12. Qualitative methods (Linda Finlay) -- 13. How to use thematic analysis with interview data (Virginia Braun, Victoria Clarke & Nicola Rance) -- 14. Case study methodologies (Julia McLeod, Mhairi Thurston & John McLeod) -- 15. How to use case study methodology with single client therapy data (Mhairi Thurston, Julia McLeod & John McLeod) -- pt. IV Completing the research journey -- 16. Dissemination of research (Andrew Reeves) -- 17. Student top tips (Brian Sreenan, Harriet Smith & Charles Frost) -- 18. Next steps: Building on and using research in training and practice (Peter Stratton, Naomi Moller & Andreas Vossler)
Includes bibliographical references and index.
Keywords: Counseling -- Research -- Methodology; Psychotherapy -- Research -- Methodology